Unpacking the effects of scams in marketplace lending: Investor confidence and attention - Jianwen Li; Yang Zhou; Jinyan Hu (Journal of Applied Economics, 2024)
Both transformational and problematic platforms, corresponding to moderate and severe scam conditions, are considered abnormal in Chinese marketplace lending. This paper examines the impact of scams in marketplace lending on investor confidence and attention. We find that as the abnormal platform ratio increases, lenders are more likely to lose confidence and withdraw investments. They also become more concerned about the risks associated with marketplace lending and the entire industry. These effects are primarily driven by severe scam conditions. Additionally, the effects of severe scam conditions on investment withdrawals and industry-related news searches are contemporaneous, while there is a lag in the effects on searching for risk-related news. Furthermore, we also find that regulatory policies enhance individual sensitivity to severe scams, and severe scams result in greater capital outflows in first-tier regions and more significant levels of panic in other regions.
Keywords: 330; investor attention; investor confidence; marketplace lending; Scam